Peranan BUMDes Badan Usaha Milik Desa Dalam pemberdayaan ekonomi masyarakat di desa pinabetengan utara kecamatan tompaso barat - Angelina Sondakh; Iwan Kandori; Allen Ch. Manongko (Literacy: Jurnal Pendidikan Ekonomi, 2025)
< p> < p> < p> The purpose of this study was to determine how effective the role of bumdes village owned enterprises is in empowering the community s economy in Pinabetengan Utara Village Tompaso Barat District The method used by the author is a Qualitative method the Research Location is in Pinabetengan Utara Village Tompaso Barat District Data sources are Primary and Secondary data Data collection techniques used by the author are data reduction data presentation and drawing conclusions The results of the study obtained are that the role of Village Owned Enterprises is very much needed because it can provide convenience for the community in Pinabetengan Utara Village in increasing the empowerment of the Community s Economy Keywords: Role of Bumdes Community Economic Empowerment < p>